Genetic activation of Nrf2 reduces cutaneous symptoms in a murine model of Netherton syndrome - Sukalp Muzumdar; Michael Koch; Hayley Hiebert; Andreas Bapst; Alessia Gravina; Wilhelm Bloch; Hans-Dietmar Beer; Sabine Werner; Matthias Schäfer (The Company of Biologists, 2020)
Netherton syndrome is a monogenic autosomal recessive disorder primarily characterized by the detachment of the uppermost layer of the epidermis, the stratum corneum. It results from mutations in the SPINK5 gene, which codes for a kallikrein inhibitor. Uncontrolled kallikrein activity leads to premature desquamation, resulting in a severe epidermal barrier defect and subsequent life-threatening systemic infections and chronic cutaneous inflammation. Here, we show that genetic activation of the transcription factor nuclear factor (erythroid-derived 2)-like 2 (Nfe2l2/Nrf2) in keratinocytes of Spink5 knockout mice, a model for Netherton syndrome, significantly alleviates their cutaneous phenotype. Nrf2 activation promoted attachment of the stratum corneum and concomitant epidermal barrier function, and reduced the expression of pro-inflammatory cytokines such as tumor necrosis factor α and thymic stromal lymphopoietin. Mechanistically, we show that Nrf2 activation induces overexpression of secretory leukocyte protease inhibitor (Slpi), a known inhibitor of kallikrein 7 and elastase 2, in mouse and human keratinocytes in vivo and in vitro, respectively. In the Spink5-deficient epidermis, the upregulation of Slpi is likely to promote stabilization of corneodesmosomes, thereby preventing premature desquamation. Our results suggest pharmacological NRF2 activation as a promising treatment modality for Netherton syndrome patients. This article has an associated First Person interview with the first author of the paper.